2020
DOI: 10.1186/s12943-020-01172-y
|View full text |Cite
|
Sign up to set email alerts
|

The emerging roles of N6-methyladenosine (m6A) deregulation in liver carcinogenesis

Abstract: Liver cancer is a common cancer worldwide. Although the etiological factors of liver carcinogenesis are well defined, the underlying molecular mechanisms remain largely elusive. Epigenetic deregulations, such as aberrant DNA methylation and histone modifications, play a critical role in liver carcinogenesis. Analogous to DNA and core histone proteins, reversible chemical modifications on mRNA have recently been recognized as important regulatory mechanisms to control gene expression. N6-methyladenosine (m6A) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
193
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 244 publications
(209 citation statements)
references
References 102 publications
4
193
1
Order By: Relevance
“…Moreover, high expression of HNRNPA2B1 and low expression of ALKBH5 were indicated as the risk factor for the survival of ESCA, and the combination of these two factors showed more predictive potential than the alone, although the ROC curve did not show robust prediction within 4 and 5 years, which because of that there are too few patients in the fourth and fifth years, which may lead to the instability of the ROC curve. It is reported that HNRNPA2B1 could selectively bind to m 6 A-containing transcripts via the “m 6 A-switch,” a mechanism in which m 6 A weakens Watson–Crick base pairing to destabilize the RNA hairpin structure and thereby exposes the single stranded hnRNP binding motif ( 37 ). HNRNPA2B1 has been reported to be a RNA-binding protein involved in different cancer progression ( 38 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, high expression of HNRNPA2B1 and low expression of ALKBH5 were indicated as the risk factor for the survival of ESCA, and the combination of these two factors showed more predictive potential than the alone, although the ROC curve did not show robust prediction within 4 and 5 years, which because of that there are too few patients in the fourth and fifth years, which may lead to the instability of the ROC curve. It is reported that HNRNPA2B1 could selectively bind to m 6 A-containing transcripts via the “m 6 A-switch,” a mechanism in which m 6 A weakens Watson–Crick base pairing to destabilize the RNA hairpin structure and thereby exposes the single stranded hnRNP binding motif ( 37 ). HNRNPA2B1 has been reported to be a RNA-binding protein involved in different cancer progression ( 38 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…6-8 m 6 A modification is installed by methyltransferases (termed as "m 6 A writers"), removed by demethylases (termed as "m 6 A erasers") and recognized by binding proteins (termed as "m 6 A readers"). 9,10 One class of direct and robust m 6 A readers are proteins containing the YTH domain, including YTHDF1-3 and YTHDC1-2. 11,12 Figure 1 YTHDC2 is downregulated in NSCLC tissues and cell lines.…”
Section: Introductionmentioning
confidence: 99%
“…The occurrence and development of HCC involve interactions between genetics, epigenetics, and transcriptomic alterations (Aravalli et al, 2013). Epigenetic dysregulation promotes the initiation and progression of HCC (Chen and Wong, 2020).…”
Section: Introductionmentioning
confidence: 99%